2018
DOI: 10.1186/s12904-018-0354-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of trained laypersons in end-of-life or advance care planning conversations: a qualitative meta-synthesis

Abstract: BackgroundLaypersons including volunteers, community health navigators, or peer educators provide important support to individuals with serious illnesses in community or healthcare settings. The experiences of laypersons in communication with seriously ill peers is unknown.MethodsWe performed an ENTREQ-guided qualitative meta-synthesis. We conducted a systematic search of MEDLINE, PsycINFO, CINAHL, Cochrane Library, and AMED to include qualitative studies with data regarding communication and laypersons in adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…While individual consideration of future EoL issues is also likely to take place in Sweden, the lack of systematic practice motivates consideration of the Swedish context itself as ACP-naive on a collective level. Based on previous international research and adapted to the Swedish context, the approach to ACP in this research project: “Advance care planning in Sweden” (SweACP), is based on three cornerstones as it is (a) conversation-based ( Sudore & Fried, 2010 ; Vearrier, 2016 ), (b) initiated early ( Howard et al, 2015 ; Zwakman et al, 2018 ), and (c) community-based, that is, taking place outside the health and social care systems ( Litzelman et al, 2017 ; Somes et al, 2018 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While individual consideration of future EoL issues is also likely to take place in Sweden, the lack of systematic practice motivates consideration of the Swedish context itself as ACP-naive on a collective level. Based on previous international research and adapted to the Swedish context, the approach to ACP in this research project: “Advance care planning in Sweden” (SweACP), is based on three cornerstones as it is (a) conversation-based ( Sudore & Fried, 2010 ; Vearrier, 2016 ), (b) initiated early ( Howard et al, 2015 ; Zwakman et al, 2018 ), and (c) community-based, that is, taking place outside the health and social care systems ( Litzelman et al, 2017 ; Somes et al, 2018 ).…”
mentioning
confidence: 99%
“…There is an extensive body of research on ACP, particularly from English-speaking countries, for example, on ACP interventions and programs ( Carter et al, 2018 ; Sudore, Schillinger, et al, 2018 ), facilitators’ and target persons’ experiences of engaging in ACP ( Howard et al, 2018 ; Somes et al, 2018 ), and ACP in different minority populations ( Laury, Mackenzie-Greenle, & Meghani, 2019 ; Sudore, Cuervo, et al, 2018 ). However, surprisingly little has been published about the actual content of ACP conversations and how values and preferences are discussed by individuals ( Hirakawa, Chiang, Hilawe, & Aoyama, 2017 ; Robinson, Hart, & Sanders, 2019 ).…”
mentioning
confidence: 99%
“…[13][14][15][16][17] The ability to communicate effectively is a critical determinant of the success of LHWs in most of these roles. 6,13,14,18 When caring for African Americans with life-limiting illnesses, LHWs often face significant communications barriers. For many African Americans, conversations with health professionals and within families about death and dying only occur once death is pending; thus compressing the ACP period.…”
Section: Introductionmentioning
confidence: 99%
“…24 Instead, LHWs caring for persons with life-limiting illnesses have sometimes felt unprepared, expressing ''a lack of confidence to meet the overwhelming needs of people with serious illness.'' 17,18,23 Spiritual and religious concerns should be anticipated when supporting persons with life-limiting illnesses. Interviews of patients with serious or life-limiting illnesses revealed that ''attending to spiritual and religious concerns'' was the most important of seven domains that influence preferences for care at the end of life, and the significance of this domain was most strong among African Americans.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Trained laypersons can support ACP among general older adult populations and disease-specific populations, 9,11 although a qualitative metasynthesis found that no programs focused on layperson communication skills training. 11 Using key principles of community-based participatory research, [12][13][14] relationship-centered approaches to communication, [15][16][17][18] expertise in community-based ACP using laypersons, 11 and a long-standing community-academic partnership, the program objectives were to develop, test, and evaluate an ACP Community Guides Program that rigorously trains individuals to initiate ACP conversations within their own communities. Recognizing the need to improve both the quality and the quantity of ACP, this study aimed to develop, test, and evaluate an ACP Community Guides Program that trains individuals to engage in relationship-centered ACP conversations.…”
Section: Introductionmentioning
confidence: 99%